2022
DOI: 10.1186/s12870-022-03509-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics of wild and commercial Citrus during early ripening reveals how domestication shaped fruit gene expression

Abstract: Background Interspecific hybridizations and admixtures were key in Citrus domestication, but very little is known about their impact at the transcriptomic level. To determine the effects of genome introgressions on gene expression, the transcriptomes of the pulp and flavedo of three pure species (citron, pure mandarin and pummelo) and four derived domesticated genetic admixtures (sour orange, sweet orange, lemon and domesticated mandarin) have been analyzed at color break. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 146 publications
(171 reference statements)
0
9
0
Order By: Relevance
“…Thus, the KEGG data show that gene expression of practically all genes encoding enzymatic activities involved in glycolysis (Supplementary Figure 4 4.002), and several subunits of the major regulatory complex of the oxidative phosphorylation process (Supplementary Figure 4.014) were upregulated in the papeda. As in SCM, in the highly acidic species lemon and citron, several genes involved in the TCA cycle and GABA shunt also displayed reduced expression during ripening (Borredá et al, 2022). Based on these observations, we propose that in the papeda, the generation of energy in the ATP form, is stimulated through the increase of the carbon flux via both glycolysis and fatty acid degradation, generating pyruvate and acetyl CoA, respectively, to fuel the Krebs cycle (Figure 6).…”
Section: Differential Gene Expression In Ichang Papeda Versus Sun Chu...mentioning
confidence: 79%
See 2 more Smart Citations
“…Thus, the KEGG data show that gene expression of practically all genes encoding enzymatic activities involved in glycolysis (Supplementary Figure 4 4.002), and several subunits of the major regulatory complex of the oxidative phosphorylation process (Supplementary Figure 4.014) were upregulated in the papeda. As in SCM, in the highly acidic species lemon and citron, several genes involved in the TCA cycle and GABA shunt also displayed reduced expression during ripening (Borredá et al, 2022). Based on these observations, we propose that in the papeda, the generation of energy in the ATP form, is stimulated through the increase of the carbon flux via both glycolysis and fatty acid degradation, generating pyruvate and acetyl CoA, respectively, to fuel the Krebs cycle (Figure 6).…”
Section: Differential Gene Expression In Ichang Papeda Versus Sun Chu...mentioning
confidence: 79%
“…During the last years, most attention has been paid to the identification of genes or gene families impacting palatability traits, fruit characteristics and reproductive behavior. Among the palatability traits, wide evidence indicates that domestication has modulated pivotal genes regulating major components of citrus flavor, such as acidity (Butelli et al, 2019;Strazzer et al, 2019;Feng et al, 2021;Borredá et al, 2022), bitterness (Chen et al, 2021) or sweetness (Li et al, 2019;Feng et al, 2021). Domestication also appears to have reduced certain chemical defenses in citrus (Gonzalez-Ibeas et al, 2021a,b;Rao et al, 2021), as reported in many crops (Köllner et al, 2008;Yactayo-Chang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carotenoids have special relevance to human nutrition and health-related aspects of immunity enhancement, eyes protection, and cancer and cardiovascular disease prevention ( Figure 3 ) ( 10 ). As an important source of natural carotenoids, citrus carotenoids not only contribute nutritional value to citrus fruits, but also are responsible for the attractive color of yellow, orange, and red ( 10 , 70 ). Carotenoids are naturally occurring fat-soluble pigments with antioxidant functions and some of them (provitamin A carotenoids, including α-carotene, β-carotene, and β-cryptoxanthin) can be converted into vitamin A (retinol) ( 71 ), thus make citrus become a valuable source to fulfill the recommended daily ingestion specifications.…”
Section: Phytochemical Profiles Of Citrusmentioning
confidence: 99%
“…Overexpression of FaSUT1 in strawberry fruit may increase both sucrose and ABA content and accelerate fruit ripening (Jia et al, 2013). OMT (O-methyltransferase) is a flavonoid-modifying enzyme that determines the diversity of flavonoids (Borredáet al, 2022). The expression of MdoOMT1 increases strongly with ethylene and is correlated with increased estragole production in ripened apples (Yauk et al, 2015).…”
Section: Fvearf2 Affects Strawberry Fruit Ripening and Qualitymentioning
confidence: 99%